Islamic banking's contribution to the Malaysian real economy - Ibrahim Musa Gani; Zakaria Bahari (ISRA International Journal of Islamic Finance, 2021)
Purpose - Malaysia is one of the fastest-growing Asian economies with a properly designed and developed Islamic financial system. This unique feature of the Malaysian economy made it an important case study, and the purpose of this study is to assess for the dynamic contribution of Islamic finance to the growth of the real economy. Design/methodology/approach - The study uses a quarterly data set of 20 years analysed via the autoregressive distributive lag bounds test approach to cointegration. Findings - The results in the short-run show a non-significant relationship between Islamic banking indices and the real economy. However, in the long-run, financing and deposits of Islamic banks are favourable and contribute significantly to the growth of the Malaysian economy. There was an accumulation of meaningful and wide-ranging investment over the period of the study and productivity of capital was also extra-efficient. The direction of causality is found to be bidirectional between Islamic banking deposits and Malaysian gross domestic product (GDP), but there is aweak causal effect fromIslamic banking financing to GDP. Research limitations/implications - Malaysia has a dual financial system (conventional and Islamic) and both can affect its real economy. This research is limited to Islamic banking's effects on Malaysian economic growth. The research also limits the scope and coverage for 20 years, from 1998 to 2017 to cover the years for which data is available for all the variables used in the study. Practical implications - The results confirm that the Islamic banking sector in Malaysia is performing well in carrying out its major function of financial intermediation, which is the pooling and channelling of funds to productive investment activities. Consequently, the fact that Malaysia excels in Islamic finance is not a fluke. It is because of the effective performance of Islamic financial institutions in the country. Furthermore, Malaysian authorities are doing their level best in promoting Islamic financial activities. Originality/value - The study fulfills the need to uncover the relationship between the Islamic financial system and the real economy in Malaysia. It differs from other studies as it uses the most recent available data, introduces new variables and identifies the channel by which Islamic banking development transmits growth.
Keywords: 330; Capital accumulation and productivity of capital; Deposits; Economic growth; Financing; Islamic banking; Islamic finance